2011
DOI: 10.1002/bit.24396
|View full text |Cite
|
Sign up to set email alerts
|

Increased matrix synthesis by fibroblasts with decreased proliferation on synthetic chitosan–gelatin porous structures

Abstract: Influence of mechanical characteristics and matrix architecture of substrates used in cell culture is an important issue to tissue engineering. Chitosan-based materials have been processed into porous structures, injectable gels and membranes, and are investigated to regenerate various tissues. However, the effect of these structures on cell growth and matrix production in accordance with each of the differing scaffolds has not been examined. We investigated the influence of porous structures, hydrogels, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 78 publications
0
30
0
1
Order By: Relevance
“…In such conditions, HGF proliferation capability is maximal, while Collagen I secretion level is low. In fact it is well known that cell growth on a polystyrene surface is optimized at the expense of matrix component production and assembly 30,31) . On the contrary, in an in vivo condition, cells show a minimal proliferation rate while they are very active in matrix production.…”
Section: Discussionmentioning
confidence: 99%
“…In such conditions, HGF proliferation capability is maximal, while Collagen I secretion level is low. In fact it is well known that cell growth on a polystyrene surface is optimized at the expense of matrix component production and assembly 30,31) . On the contrary, in an in vivo condition, cells show a minimal proliferation rate while they are very active in matrix production.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the authors have shown that viability can be accurately assessed by prestaining the cells with CFDA-SE and measuring the cytoplasmic content at a predetermined time. 37 Also, cell division could be tracked using CFDA-SE and flow cytometry. Cytoplasmic content depicts the viable cells present in the scaffolds.…”
Section: Cell Viability and Attachmentmentioning
confidence: 99%
“…full-thickness skin). The type of natural or synthetic polymer used for hydrogel preparation is a critical factor in determining cell-material interactions, mechanical properties, fluid permeability and, subsequently, promotion of angiogenesis [6] . For example, inflammation has been directly associated with the host angiogenic response with evidence which indicates a slight pro-inflammatory response may be necessary for the stimulation of angiogenesis in the implant site [7] .…”
Section: Introductionmentioning
confidence: 99%